Linagliptin inhibits lipopolysaccharide-stimulated interleukin-6 production, intranuclear p65 expression, and p38 mitogen-activated protein kinase phosphorylation in human umbilical vein endothelial cells. Issue 1 (December 2016) - Nakamura, Yuya; Hasegawa, Hitomi; Tsuji, Mayumi; Oguchi, Tatsunori; Mihara, Masatomo; Suzuki, Hiroki; Nishida, Kazumasa; Inoue, Michiyasu; Shimizu, Tatsuo; Ohsawa, Isao; Gotoh, Hiromichi; Goto, Yoshikazu; et al.
Abstract Background Linagliptin, the only bile-excreted dipeptidyl peptidase-4 (DPP-4) inhibitor, is a therapeutic drug for patients with diabetes receiving hemodialysis, for whom inflammation is a prognosis-related factor, because of its potential anti-inflammatory effects. Although the anti-inflammatory effects of linagliptin in vivo are reported, no study has described these effects in vitro. DPP-4 degrades glucagon-like peptide-1 (GLP-1), which is known to have anti-inflammatory properties. Since GLP-1 is a gut hormone secreted by intestinal L cells, in vivo examination of the GLP-1-independent anti-inflammatory effects of DPP-4 inhibitors is difficult. We evaluated the mitogen-activated protein kinase (MAPK)-dependent, GLP-1-independent, anti-inflammatory effects of linagliptin in lipopolysaccharide (LPS)-stimulated human umbilical vein endothelial cells (HUVECs) which do not secrete GLP-1. Furthermore, to determine whether linagliptin has unique pharmacological actions compared with other DPP-4 inhibitors, we assessed the anti-inflammatory effects of sitagliptin (a DPP-4 inhibitor without xanthine-related skeletal system activity), caffeine (a phosphodiesterase inhibitor), loxoprofen, and diclofenac sodium. Methods HUVECs were cultured for 24 h at densities of 1–2 × 105  cells/mL. We pretreated HUVECs with or without linagliptin (1, 5, 10, 50, and 100 nM), 150 nM sitagliptin, 50 nM caffeine, 17 μM loxoprofen, or 1.3 μM diclofenac sodium for 1 h prior to incubation with LPS. The concentration of LPS used (1 μg/mL) was sufficient to induce an inflammatory response in HUVECs. Five hours after incubation with LPS, culture media was evaluated for interleukin (IL)-6 expression. Intranuclear p65 (a subunit of nuclear factor kappa-B (NFκB)) levels were measured 5 h after treatment with LPS and 50 nM linagliptin, while phosphorylated p38 MAPK levels were measured in the cytosolic fractions obtained 30 min after treatment with LPS and 50 nM linagliptin. Results Linagliptin significantly inhibited LPS-stimulated IL-6 production, intranuclear p65 expression, and p38 MAPK phosphorylation. Treatment with sitagliptin, caffeine, loxoprofen, and diclofenac sodium significantly inhibited LPS-stimulated IL-6 production. Conclusions The results of this study demonstrate the GLP-1-independent anti-inflammatory effects of linagliptin via MAPK-dependent mechanisms in vitro. Our findings suggest that linagliptin will play a crucial role in the treatment of hemodialysis (HD) patients with diabetes and chronic inflammation.